2023
DOI: 10.1002/adfm.202301351
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Doped Mn/Mo Oxides with Core‐Shell Structures Designed by a Self‐Template Strategy for Durable Aqueous Zinc‐Ion Batteries

Abstract: Manganese oxide as the star cathode material of aqueous zinc ion batteries is vigorously developed because of its environmental protection, outstanding theoretical capacity, and high voltage. However, severe Jahn–Teller distortion of trivalent Mn has detrimental effect on cyclic stability. Herein, 1D core‐shell bimetal oxide with cross‐doping of heteroatom is successfully designed by self‐template method via one‐step hydrothermal reaction. Specifically, the thick shell of Mo‐doped α‐MnO2 with increased nanopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The bimetallic oxides are composed of Mo-doped α-MnO 2 nanoparticles as the shell and Mn-doped MoO 3 nanobelts as the core, exhibiting the advantages of large specific surface area, resistance to mechanical deformation, and enlarged diffusion channels. 39…”
Section: Introductionmentioning
confidence: 99%
“…The bimetallic oxides are composed of Mo-doped α-MnO 2 nanoparticles as the shell and Mn-doped MoO 3 nanobelts as the core, exhibiting the advantages of large specific surface area, resistance to mechanical deformation, and enlarged diffusion channels. 39…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated the enhanced intrinsic properties of energy storage materials through the introduction of heteroatom doping or functional group modification. This is commonly achieved through various methodologies, including high temperature sintering, 1,2 co-precipitation, 3,4 hydrothermal reactions, 5–7 vapor deposition (CVD/PVD), 8,9 chemical reactions, and other similar approaches. These techniques lead to improvements in specific capacity, initial efficiency, and rate capability of energy storage materials by inducing the formation of defects, vacancies, active sites, 10 etc.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is particularly common in aqueous zinc-ion batteries (AZIBs) with MnO 2 as the cathode material. To solve these problems, a series of effective strategies have been developed, such as heteroatom doping, defect engineering, bond/interface engineering, nanostructure design, electrolyte modification, and surface coating. …”
Section: Introductionmentioning
confidence: 99%